Measurement of concrete layer thickness by using an ultrasonic technique / Safari Zainal - Zainal, Safari (2000)
The objective of this project is to introduce a new technique in measuring concrete layer thickness. Ultrasonic testing is used as an alternative method to the ordinary method such as Boring technique. The effectiveness of the application of the surface wave method is also being studied. The ultrasonic testing will be use on concretes sample at frequency of 50 kHz by using PUNDIT and FLUKE 99 Scopemeter Series II. The use of this concept of multiple correlations for measuring the thickness of concrete is evident both directly for the assessment and control of the concrete quality. Results obtained from measurement by using an ultrasonic method show good relationship with actual thickness of concrete.